Proceedings of the Sixth ACM SIGSPATIAL International Workshop on Indoor Spatial Awareness - ISA '14 2014
DOI: 10.1145/2676528.2676535
|View full text |Cite
|
Sign up to set email alerts
|

Insar

Abstract: Indoor navigation applications for mobile devices are being more common and needed for people who want to find inside building destinations. Many indoor navigation applications utilize different technologies, such as Wi-Fi fingerprinting, have been suggested. Most of these applications use a fixed background map and pre-calculated paths to lead the user to their destinations. Users of these systems need general map reading skills and understanding how specifically indoor maps work. In addition, these system ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 28 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Navigation systems should provide notifications and alerts to guide users in finding their destination [85][86][87]. Previous research has shown that a lack of visual or audio notification upon arrival at a destination can lead to failure in recognizing the target location by participants [88].…”
Section: Notifications and Alertsmentioning
confidence: 99%
See 1 more Smart Citation
“…Navigation systems should provide notifications and alerts to guide users in finding their destination [85][86][87]. Previous research has shown that a lack of visual or audio notification upon arrival at a destination can lead to failure in recognizing the target location by participants [88].…”
Section: Notifications and Alertsmentioning
confidence: 99%
“…It is useless to notify the user when they are not in the area or notify when they have already passed the area. Alnabhan and Tomaszewski [86] highlighted the importance of the accuracy of displayed notifications. They developed an AR-based indoor navigation system, "INSAR", that issues a 2 s notification vibration when it finds the destination and displays a message telling the user that they have arrived at their destination [86].…”
Section: Notifications and Alertsmentioning
confidence: 99%
“…These application types are perfect to guide the user outdoors by revealing the directions and distance between the user and their destination. In enclosed places such as buildings, airports, and markets, however, GPS satellite signals become weak or non-existent; therefore, GPS is not suitable for indoor positioning and navigation (Alnabhan, 2014). 64 museum mobile applications from around the world were evaluated in 2011 in the survey "Promising beginnings?…”
Section: Digital Navigational Assistantsmentioning
confidence: 99%
“…Signs would be accessible on the requested path, identifiable when they appear on the visitor's eye level, and understandable in the chosen language. The computer-generated elements can be 2D or 3D graphics, text, audio or video that augment and integrate with the physical world to reveal useful information to the user (Alnabhan, 2014).…”
Section: Digital Navigational Assistantsmentioning
confidence: 99%
See 1 more Smart Citation